Aerial-Aquatic Locomotion in Nature - Zufferey,R; Siddall,R; Armanini,SF; Kovac,M (2022)
Water covers 363 million square km, or 72% of the earth’s surface. The vast majority of this water is saline (96%), frozen (2%) or groundwater (1%). The 10 5 km 3 of surface freshwater (0.008%) is in turn concentrated almost entirely in three large great lake systems (Fig. 3.1), with a vanishing small amount of surface freshwater forming lakes and rivers.